Genetikai teszt a fogyasztók számára - Tárczy, Edit Zsuzsanna (Debreceni Jogi Műhely, 2013)
The European Academies Science Advisory Council (hereafter: EASAC) and the Federation of European Academies of Medicine (hereafter: FEAM) published a study on „Direct-toconsumer genetic testing for health-related purposes in the European Union” in the summer of 2012. This paper shows the results of the research of the working group of the two mentioned organizations. The main aim was to investigate the scientific, ethic questions and the questions in connection with the possible regulation. The second aim was to define principles and recommendations for the European Commission, the European Parliament, the Council of Ministers and the political decision-makers of the Member States. This paper also shows the results of the workshop – organized by the EASAC, the FEAM and the Science and Technology Options Assessment (hereafter: STOA) - in the end of 2012. Finally, there are some facts on the regulations on the genetic tests outside the EU.